Dance and Embodied Cognition: Motivations for the Enactivist Program - Carmona, Carla (Rivista Italiana di Filosofia del Linguaggio, 1970)
This paper examines dance instruction and choreographic work within Western contemporary dance practice. Its goal is to re-contextualize the later Wittgenstein’s ideas regarding the nature of our linguistic competence and cognitive abilities at large in the light of the rise of enactivism. I discuss examples within dance practice that show that cognition is distributed across brain, body and environment. In the process, this paper supports a good number of sensorimotor enactivism’s fundamental claims. However, its main purpose is to bring insight into embodied cognition that is non-representational at root, which could motivate the radical version of enactivism. In this regard, I provide evidence against the conception of perceptual experience as like snapshots. I also argue that sensorimotor enactivism – due to its focus on visual experience – is held captive by such a picture, despite its battle against it. In this regard, I refute sensorimotor enactivism’s idea that practical knowledge mediates in perceptual experience by means of examples. I explore instances of non-conceptual, non-mediated perceptual experience that are a product of embodied engagements with the environment. As a result, I propose an enactivist view of embodied cognition that accounts for non-representational processes.